The Translation of National Identity in the Iraqi Official Statements (Journal of the College of Education for Women, 2024)
This paper investigates the translation of national identity in the Iraqi official statements. The main problem is that the Iraqi translator may be not aware of the structure of national identity that the necessary parts of the political text may be omitted through translation. One of the most important objectives is to identify whether the Iraqi translator is conscious of the national identity dimensions in the political texts, and whether he/she is keen enough to render these dimensions in the translated versions. The quantitative research design is used in this paper. The adopted model is Wodak et al. (2009) which is used to analyze the construction of Austrian national identity. It has been concluded that the Iraqi translators have succeeded in transferring the Iraqi national identity from the source text into the target text and that they adopt the appropriate strategies in translating political texts. Borrowing is used as a translation strategy in rendering the culture-bound terms from Arabic lexicon which are related to religion such as fatwa, jihad, Ayatollah into English language.